A multi-technique approach to characterization: the Sant Martí de Tous chert as a prehistoric resource for the NE of the Iberian Peninsula - Gómez de Soler, Bruno (2023)
The Sant Genis Formation is located in the NE of the Iberian Peninsula (Catalonia, Spain) and is dated to the Priabonian (upper Eocene), being part of the evaporitic formations of the margin of the Ebro Basin. It is formed by a succession of sandy lutites, occasional limestone layers, marls, and local stratified gypsum and cherts, including the Sant Marti de Tous chert. The Sant Marti de Tous chert type is confirmed by its abundance at specific locations within the territory (NE Iberian Peninsula). This is an important raw material procurement area, as evidenced by the presence of this chert in the main prehistoric sites of the region (e.g., Abric Romani) and the constant discovery of new sites in the area around the Sant Genis Formation, especially from the Neolithic period onwards (e.g., Cal Sitjo, La Guinardera Nord workshop). All these features, together with the great heterogeneity of the Cenozoic evaporitic cherts, prompted us to carry out a multi-proxy characterization for obtaining a valid criterion by which to identify this chert in the archaeological record. This very heterogeneity hampers the macroscopic characterization of archaeological cherts (e.g., at Abric Romani), but through petrographic analysis we have been able to identify their origins and, albeit to a lesser extent, their lithostratigraphic unit of provenance within the formation. The complementary mineralogical and geochemical techniques applied in this study show that, although it is difficult to establish an exact origin, through intensive sampling and criteria such as the differential presence of Fe and Ca, some differences among the siliceous varieties within a formation can be detected.